Optimizing strategies to identify high risk of developing type 2 diabetes - Bracco, Paula Andreghetto; Schmidt, Maria Inês; Vigo, Alvaro; Mill, José Geraldo; Vidigal, Pedro Guatimosim; Barreto, Sandhi Maria; Sander, Mária de Fátima; da Fonseca, Maria de Jesus Mendes; Duncan, Bruce Bartholow (Frontiers in Endocrinology, 2023)
Abstract Introduction: The success of diabetes prevention based on early treatment depends on high-quality screening. This study compared the diagnostic properties of currently recommended screening strategies against alternative score-based rules to identify those at high risk of developing diabetes. Methods: The study used data from ELSA-Brasil, a contemporary cohort followed for a mean (standard deviation of 7.4 (0.54) years, to develop risk functions with logistic regression to predict incident diabetes based on socioeconomic, lifestyle, clinical, and laboratory variables. We compared the predictive capacity of these functions against traditional pre-diabetes cutoffs of FPG, 2hPG, and HbA1c alone or combined with recommended screening questionnaires. Results: Presenting FPG>100mg/dl predicted 76.6% of future cases of diabetes in the cohort at the cost of labeling 40.6% of the sample as high-risk. If FPG testing was done only in those with a positive ADA questionnaire, labeling was reduced to 12.2%, but only 33% of future cases were identified. Scores using continuously expressed clinical and laboratory variables produced a better balance between detecting more cases and labeling fewer false positives. They consistently outperformed strategies based on categorical cutoffs. For example, a score composed of both clinical and laboratory data, calibrated to detect a risk of future diabetes >20%, predicted 54% of future diabetes cases, labeled only 15.3% as high-risk, and, compared to the FPG≥100mg/dl strategy, nearly doubled the probability of future diabetes among screen-positives. Discussion: Currently recommended screening strategies are inferior to alternatives based on continuous clinical and laboratory variables.